2013
DOI: 10.7314/apjcp.2013.14.4.2237
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Applied Progressive Deep Muscle Relaxation Training on the Level of Depression, Anxiety and Stress among Prostate Cancer Patients: A Quasi-Experimental Study

Abstract: Background: The aim of this study was to determine the impact of applied progressive muscle relaxation training on the levels of depression, anxiety and stress among prostate cancer patients. Materials and Methods: A quasi-experimental study was conducted at the University Malaya Medical Centre (UMMC) and Universiti Kebangsaan Malaysia Medical Centre (UKMMC) over six months. Prostate cancer patients from UMMC received the intervention and patients from UKMMC were taken as controls. The level of depression, anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
3
19
1
1
Order By: Relevance
“…Furthermore [36] reported that after the treatment, the anxiety score of study subjects was significantly lower than before. The results were contradicted with Rodi et al [37] who stated that there were no significant changes in depression when compare results of both groups. This discrepancy may be attributed to the difference in sampling techniques and different measuring tools.…”
Section: Regarding Depression Anxiety and Stress Scores (Seecontrasting
confidence: 56%
“…Furthermore [36] reported that after the treatment, the anxiety score of study subjects was significantly lower than before. The results were contradicted with Rodi et al [37] who stated that there were no significant changes in depression when compare results of both groups. This discrepancy may be attributed to the difference in sampling techniques and different measuring tools.…”
Section: Regarding Depression Anxiety and Stress Scores (Seecontrasting
confidence: 56%
“…PMR exercise is a nursing intervention that is used to manage or reduce cancer-related symptoms. PMR is able to reduce anxiety and stress level in patients with prostate malignancy (p value < 0.001) [17]. PMR exercise is able to improve an individual's capacity to manage various stressful circumstances and increase self-control [18].…”
Section: Discussionmentioning
confidence: 98%
“…PMR was developed by the American physician Edmund Jacobson at the beginning of the 20 th century (46). Since then, short forms and modifications of this relaxation technique have often been used and have been shown to have positive psychophysiological effects in the general population and in patients with somatic and psychological diseases (48)(49)(50)(51)(52). PMR includes the tension of certain muscle-groups followed by the subsequent relaxation of these muscles.…”
Section: Relaxation Trainingsmentioning
confidence: 99%